Ab initio thermodynamic approach to identify mixed solid sorbents for CO2 capture technology - Duan, Yuhua (Frontiers in Environmental Science, 2015)
Because the current technologies for capturing CO2 are still too energy intensive, new materials must be developed that can capture CO2 reversibly with acceptable energy costs. At a given CO2 pressure, the turnover temperature (Tt) of the reaction of an individual solid that can capture CO2 is fixed. Such Tt may be outside the operating temperature range (ΔTo) for a practical capture technology. To adjust Tt to fit the practical ΔTo, in this study, three scenarios of mixing schemes are explored by combining thermodynamic database mining with first principles density functional theory and phonon lattice dynamics calculations. Our calculated results demonstrate that by mixing different types of solids, it’s possible to shift Tt to the range of practical operating temperature conditions. According to the requirements imposed by the pre- and post- combustion technologies and based on our calculated thermodynamic properties for the CO2 capture reactions by the mixed solids of interest, we were able to identify the mixing ratios of two or more solids to form new sorbent materials for which lower capture energy costs are expected at the desired pressure and temperature conditions.